Bibliografinių nuorodų statistinės analizės metodas – specialusis informatikos metodas - Voverienė, Ona (Knygotyra, 1987)
A methodology of informatics consists from methods of three levels: – a general method of scientific cognition – dialectical materialism; – general scientifical methods, common for all fields of knowledge (descriptive, logical, experimental and etc.) – special methods for that field of knowledge. There are three requirements for special methods: – a special method must be used for investigation the object of that field of knowledge; – main laws of that field of knowledge must be recovered with a help of the special method; – these laws must be used in practise for its optimization. The article is devoted to one of special methods of informatics – statistical analysis of references. One of main laws of informatics – aging of scientifical literature is recovered with help of this method. Method is used also for precising of Bredford’s law. These laws, are used in the practise of information service. The article reveals the investigations, which method of statistical analysis is used.